Positive Allosteric Modulators (PAMs) of Metabotropic Glutamate Receptor 5 (mGluR5) Attenuate Microglial Activation - Xue, Fengtian; A. Stoica, Bogdan; Hanscom, Marie; V. Kabadi, Shruti; I. Faden, Alan (CNS & Neurological Disorders - Drug Targets, 2014)
Traumatic brain injury causes progressive neurodegeneration associated with chronic microglial activation. Recent studies show that neurodegeneration and neuroinflammation after traumatic brain injury can be inhibited as late as one month in animals by the activation of the metabotropic glutamate receptor 5 in microglia using (RS)-2-chloro-5- hydroxy-phenylglycine. However, the therapeutic potential of this agonist is limited due to its relatively weak potency and brain permeability. To address such concerns, we evaluated the anti-inflammatory activities of several positive allosteric modulators using various in vitro assays, and found that 3,3’-difluorobenzaldazine, 3-cyano-N-(1,3-diphenyl-1H-pyrazol- 5-yl)benzamide and 4-nitro-N-(1-(2-fluorophenyl)-3-phenyl-1H-pyrazol-5-yl)benzamide showed significantly improved potency which makes them potential lead compounds for further development of positive allosteric modulators for the treatment of traumatic brain injury.
Keywords: traumatic brain injury